Donor‐variation effect on red blood cell storage lesion: A close relationship emerges. Issue 8 (23rd May 2016) - Tzounakas, Vassilis L.; Kriebardis, Anastasios G.; Papassideri, Issidora S.; Antonelou, Marianna H.
Abstract : Although the molecular pathways leading to the progressive deterioration of stored red blood cells (RBC storage lesion) and the clinical relevance of storage‐induced changes remain uncertain, substantial donor‐specific variability in RBC performance during storage, and posttransfusion has been established ("donor‐variation effect"). In‐bag hemolysis and numerous properties of the RBC units that may affect transfusion efficacy have proved to be strongly donor‐specific. Donor‐variation effect may lead to the production of highly unequal blood labile products even when similar storage strategy and duration are applied. Genetic, undiagnosed/subclinical medical conditions and lifestyle factors that affect RBC characteristics at baseline, including RBC lifespan, energy metabolism, and sensitivity to oxidative stress, are all likely to influence the storage capacity of individual donors' cells, although not evident by the donor's health or hematological status at blood donation. Consequently, baseline characteristics of the donors, such as membrane peroxiredoxin‐2 and serum uric acid concentration, have been proposed as candidate biomarkers of storage quality. This review article focuses on specific factors that might contribute to the donor‐variation effect and emphasizes the emerging need for using omics‐based technologies in association with in vitro and in vivo transfusion models and clinical trials to discover biomarkers of storage quality and posttransfusion recovery in donor blood.